2020
DOI: 10.1016/j.devcel.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-Phosphate Receptor Signaling Establishes AP-1 Gradients to Allow for Retinal Endothelial Cell Specialization

Abstract: Highlights d Sphingosine 1-phosphate establishes endothelial AP-1 transcription factor gradients d Sphingosine 1-phosphate signaling is needed for retinal vascular specialization d Retinal endothelial JunB regulates developmental vascular guidance and patterning d Signal-induced chromatin changes in endothelial cells regulate vascular phenotypes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 77 publications
(90 reference statements)
0
57
0
Order By: Relevance
“…These reports imply an important role for S1P1 in stabilizing sprouting angiogenesis in the retina. Consistently, S1pr1-3 triple knockout mice exhibited a disorganized retinal vascular endothelium with hyper-sprouting and a lack of vascular endothelial barrier and capillary lumens [125]. Moreover, S1pr1-3 deficient mice had insufficient blood perfusion in the retina and severe vascular structure defects due to impaired endothelial cell specialization.…”
Section: Sphingosine 1-phosphate and Ocular Neovascularizationmentioning
confidence: 78%
“…These reports imply an important role for S1P1 in stabilizing sprouting angiogenesis in the retina. Consistently, S1pr1-3 triple knockout mice exhibited a disorganized retinal vascular endothelium with hyper-sprouting and a lack of vascular endothelial barrier and capillary lumens [125]. Moreover, S1pr1-3 deficient mice had insufficient blood perfusion in the retina and severe vascular structure defects due to impaired endothelial cell specialization.…”
Section: Sphingosine 1-phosphate and Ocular Neovascularizationmentioning
confidence: 78%
“…In retinal vascular development, the genome-wide accessibility of AP-1-binding sites is epigenetically controlled by sphingosine-1-phosphate (S1P) signaling. This process alters the chromatin composition of the AP-1-binding site to become closed and inaccessible, resulting in the inhibition of JunB-related gene expression during vascular maturation in the mouse retina [ 68 ].…”
Section: Ap-1 Transcription Factor Junb In Angiogenesismentioning
confidence: 99%
“…JunB is reportedly upregulated in tip cells at the angiogenic frontier and contributes to vascular development in mouse embryonic skin [ 26 ] and retinal vasculatures [ 68 ] ( Figure 1 ). The induction of JunB expression is temporal and spatial in tip cells at the angiogenic frontier or at the branching points during vascular development.…”
Section: Ap-1 Transcription Factor Junb In Angiogenesismentioning
confidence: 99%
“…It has been demonstrated that glycolysis intermediates (eg lactate and succinate) and glycolytic enzymes (eg fructose‐6‐phosphate‐2 kinase and fructose‐2,6‐diphosphatase 3) are implicated in the regulation of angiogenesis 60 . Besides this, S1PRs have a role in the regulation of VEGF‐mediated angiogenesis (co‐ordination function) 61 . Together, S1PRs may harbour broad effects on the intestinal angiogenesis of IBD by regulating ROS, ER stress, glycolysis, VEGF signal pathway and other processes, and hence, more understanding of their specific mechanisms is of great significance to the prevention and treatment of IBD (Figure 2).…”
Section: S1prs and Intestinal Angiogenesis In Ibdmentioning
confidence: 99%